Research in the teaching of natural sciences and the environment - Aguilar, María Luisa (2021)
Analysis of educational conditions in Peru. Role of astronomy in education. Profile of courses according to the content and philosophy of educational reform for pre-school, primary, secondary, university levels, where the methods of observation, experimentation and analysis of astronomical sciences show their benefits in the application of constructivism. Organization of an Astronomical Observatory for teaching at UNMSM.